2016
DOI: 10.3151/jact.14.559
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Coupled Analysis of Interaction between Structural Deterioration and Reinforcement Corrosion by Salt Damage

Abstract: This study develops an analysis method for estimating the process of corrosion in concrete, including initial corrosion and the onset of corrosion-induced cracking. The method is suitable for application in rationalizing the verification of the durability of salt-damaged RC structures. Corrosion deterioration is computed by coupling the analysis of structure with the analysis of reinforcement corrosion. A method of calculating macro-cell corrosion in consideration of macro-cell corrosion current density is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In consideration of the passive condition of rebar in the high alkalinity of concrete pore solution and the breaking of the passive film by chloride, two parameters are adopted to characterize the anodic reaction with respect to the spontaneous potential and Tafel slope (Stern and Geary 1957;Hussain and Ishida 2011;Suzuki et al 2016), as indicated by Eqs. ( 10) and ( 11) and Fig.…”
Section:  mentioning
confidence: 99%
“…In consideration of the passive condition of rebar in the high alkalinity of concrete pore solution and the breaking of the passive film by chloride, two parameters are adopted to characterize the anodic reaction with respect to the spontaneous potential and Tafel slope (Stern and Geary 1957;Hussain and Ishida 2011;Suzuki et al 2016), as indicated by Eqs. ( 10) and ( 11) and Fig.…”
Section:  mentioning
confidence: 99%
“…Corrosion of reinforcing bars in structural concrete is a critical deterioration associated with electro-chemical reaction, which is generally classified as micro-cell circuit where anodic and cathodic polarization proceeds locally at one place, and the macro-cell one where oxidation and reduction separately progress in space with great rapidity (Suzuki et al 2016;Angst 2018). For the former case, global electric field is not necessarily solved for estimating rate of corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the previous researchers have applied galvanostatic electrolysis with current densities from 1 to 100 A/m 2 to steel rebar in concrete from 24 to a few thousand hours. [11][12][13] For example, Takaya et al applied an anodic current of 12.2 A/m 2 for 24 h, 14 and the obtained rust often contained large amount of Cl − and CaFeO 2 Cl and Fe 6 Cl 2-x (OH) 12+x were observed in the rust. These species cannot be found in the rust naturally formed in the practical service environment.…”
mentioning
confidence: 99%